KESULITAN LITERASI NUMERASI DITINJAU DARI PEMAHAMAN KONSEP DAN SELF-EFFICACY SISWA - Atika Ayuni Febiana; Danuri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze numeracy literacy learning difficulties among fifth-grade students at SD Negeri 3 Kadipiro, Yogyakarta, viewed from mathematical conceptual understanding and self-efficacy. The study focuses on identifying students’ difficulties in understanding problem contexts, interpreting mathematical information, and determining appropriate problem-solving strategies in contextual situations. It also examines the role of conceptual understanding and mathematical self-efficacy in supporting numeracy literacy skills at the elementary school level. This research employed a descriptive qualitative approach. The research subjects included the school principal, the fifth-grade teacher, and fifth-grade students at SD Negeri 3 Kadipiro. Data were collected through a conceptual understanding test, a mathematical self-efficacy questionnaire, in-depth interviews, classroom observations, and documentation. Data analysis was conducted inductively through data collection, data reduction, data presentation, and conclusion drawing with verification. Data validity was ensured through technique triangulation and source triangulation. The results indicate that students’ numeracy literacy difficulties were at a moderate level. The main difficulties involved understanding problem contexts, converting verbal language into mathematical representations, and applying systematic problem-solving steps. Students’ mathematical conceptual understanding was uneven and contributed to numeracy literacy difficulties. Although students’ mathematical self-efficacy was generally good, it was not sufficient to overcome cognitive barriers. Therefore, improving numeracy literacy requires balanced strengthening of conceptual understanding and self-efficacy through contextual and sustainable learning approaches. Keywords: Numeracy Literacy, Conceptual Understanding, Mathematical Self-Efficacy